Post-storage sensory quality of apple varieties - Kókai, Z.; Sass, P.; Erdélyi, M. (International Journal of Horticultural Science, 2001)
The changing situation of apple production in Hungary has given rise to a great demand for new varieties. Besides bearing capacity, fruit quality and suitability for new training systems, consumer preference is one of the grower's main considerations. Growers need reliable information in order to choose the appropriate variety, so consumer tests have become essential. Altogether, 1 I traditional and new varieties were involved in this project. In the first part of the experiment, panelists ranked the coded samples according to their appearance. In the second part, apples were cut into unpeeled slices and the samples were also coded. The assessors were asked to taste them and rank them again. The sensory tests were held after three different storage periods.